Regulating Conscientious Objection to Legal Abortion in Argentina: Taking into Consideration Its Uses and Consequences - Ramón Michel, Agustina (2020)
Fil: Ramón Michel, Agustina. CEDES. Centro de Estudios de Estado y Sociedad. Área de Salud, Economía y Sociedad; Argentina.